2019
DOI: 10.1016/j.trci.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of Souvenaid on cerebral glucose metabolism in Alzheimer's disease

Abstract: IntroductionAlzheimer's disease (AD) is associated with synapse loss. Souvenaid, containing the specific nutrient combination Fortasyn Connect, was designed to improve synapse formation and function. The NL-ENIGMA study explored the effect of Souvenaid on synapse function in early AD by assessing cerebral glucose metabolism (CMRglc) with 18F-fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET).MethodsWe conducted an exploratory double-blind randomized controlled single-center trial. Fifty patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(57 reference statements)
1
2
0
1
Order By: Relevance
“…The FC-like diet did not prove beneficial in any test in comparison to the control chow. This is in accordance with some clinical studies, which do not support the benefit of the FC diet and thus indicate equivocal evidence [ 73 , 74 ]. In conclusion, the beneficial tendencies we observed did not mostly reach statistical significance in behavioral tests and biochemical-/immunohistochemical analyses and consequently do not suggest a clear beneficial effect of B-vitamins or PUFAs in this mouse model at the investigated age and diet duration.…”
Section: Discussionsupporting
confidence: 89%
“…The FC-like diet did not prove beneficial in any test in comparison to the control chow. This is in accordance with some clinical studies, which do not support the benefit of the FC diet and thus indicate equivocal evidence [ 73 , 74 ]. In conclusion, the beneficial tendencies we observed did not mostly reach statistical significance in behavioral tests and biochemical-/immunohistochemical analyses and consequently do not suggest a clear beneficial effect of B-vitamins or PUFAs in this mouse model at the investigated age and diet duration.…”
Section: Discussionsupporting
confidence: 89%
“…In 52 participants from the same cohort study, a healthy nutrient pattern combining unsaturated fats; vitamins A, B12, C, D, and E; zinc; carotenoids; and fiber, was associated with increased FDG‐PET glucose metabolism 177 providing some evidence of potential key nutrients influencing brain glucose metabolism. In fact, there are emerging studies of the impact of antioxidant‐rich fruits and vegetables, n ‐3 PUFA and low‐glycemic index carbohydrates, 178 zinc, 179 fish oil supplementation rich in n ‐3 PUFA, 180 vitamins B12, E, D, PUFA, antioxidants and fibers, 177 and multi‐nutrient supplements 181,182 on FDG PET derived cerebral glucose metabolism. There are also diet patterns such a Mediterranean‐type diet that have been associated with beneficial cerebral metabolism profiles in both cross‐sectional 183 and longitudinal 176 studies.…”
Section: Evidence For Targeting Cerebral Bioenergetics Deficits In Ad...mentioning
confidence: 99%
“…but the estimated effects on outcomes related to cerebral bioenergetics such as arterial spin labeling derived cerebral blood flow, FDG PET and BOLD imaging have been limited. Measuring brain glucose metabolism with FDG PET as a proxy of neuronal activity, a few longitudinal neuroimaging studies of cognitively intake adults (aged 30-60 years) with other risk factors for AD suggested that healthy diets, such as the Mediterranean diet, or healthy nutrient patterns, influence brain glucose metabolism in mid-to-late adulthood.emerging studies of the impact of antioxidant-rich fruits and vegetables, n-3 PUFA and low-glycemic index carbohydrates,178 zinc,179 fish oil supplementation rich in n-3 PUFA,180 vitamins B12, E, D, PUFA, antioxidants and fibers,177 and multi-nutrient supplements181,182 on FDG PET derived cerebral glucose metabolism. There are also diet patterns such a Mediterranean-type diet that have been associated 15525279, 0,…”
mentioning
confidence: 99%
“…App NL-G-F Mausmodell für AD nicht bestätigt werden. Die Funde in letzterem decken sich eher mit den ebenfalls veröffentlichten negativen Berichten zu FC, insbesondere im klinischen Kontext (Shah et al, 2013;Scheltens et al, 2019). Die Evidenzlage zu FC wurde als heterogen zusammengefasst (Rasmussen, 2019).…”
Section: Roiunclassified